Changes in Membrane Dielectric Properties of Porcine Kidney Cells Provide Insight into the Antiviral Activity of Glycine - Habibi, Sanaz (Langmuir : the ACS journal of surfaces and colloids, 2020)
The ability to monitor the status and progression of viral infections is important for development and screening of new antiviral drugs. Previous research illustrated that the osmolyte glycine (Gly) reduced porcine parvovirus (PPV) infection in porcine kidney (PK-13) cells by stabilizing the capsid protein and preventing virus capsid assembly into viable virus particles. Dielectrophoresis (DEP) was examined herein as a noninvasive, electric field- and frequency-dependent tool for real-time monitoring of PK-13 cell responses to obtain information about membrane barrier functionality and polarization. DEP responses of PK-13 cells were compared to those of PPV-infected cells in the absence and presence of the osmolyte glycine. With infection progression, PK-13 DEP spectra shifted toward lower frequencies, reducing crossover frequencies (fCO). The spherical single-shell model was used to extract PK-13 cell dielectric properties. Upon PPV infection, specific membrane capacitance increased over the time progression of virus attachment, penetration, and capsid protein production and assembly. Following glycine treatment, the DEP spectra displayed attenuated fCO and specific membrane capacitance values shifted back toward uninfected PK-13 cell values. These results suggest that DEP can be used to noninvasively monitor the viral infection cycle and screen antiviral compounds. DEP can augment traditional tools by elucidating membrane polarization changes related to drug mechanisms that interrupt the virus infection cycle